Interactions between limiting nutrients: Consequences for somatic and population growth of Daphnia magna - Dominik Martin-Creuzburg; Alexander Wacker; Timo Basena (Limnology and Oceanography, 2010)
To assess the significance of nutrient interactions on animal performance, life‐history experiments were conducted with the freshwater herbivore Daphnia magna in a system with two limiting nutrients (i.e., sterols and polyunsaturated fatty acids [PUFAs]). By experimentally increasing the availability of dietary cholesterol either in the absence or in the presence of different dietary PUFAs we investigated whether dietary PUFAs differ in their potential to affect the sterol‐limited growth kinetics of the herbivore. Sterol‐limited growth responses of D. magna were characterized by a higher initial slope of the saturation curves and lower threshold concentrations in the presence of dietary PUFAs. This suggests significant interactions between limiting nutrients and lower dietary sterol requirements in the presence of dietary PUFAs. In contrast to somatic growth rates, which were significantly increased only by additional supplementation with eicosapentaenoic acid (EPA), population growth rates were significantly affected by additional supplementation with linoleic acid, α‐linolenic acid, docosahexaenoic acid (DHA), and in particular EPA and arachidonic acid. The fatty acid composition of D. magna reflected that of their diet. However, animals fed the DHA supplemented diet contained considerable amounts of EPA, indicating a retro‐conversion of DHA into EPA within their metabolism. The fitness of resource‐limited consumers is strongly affected by complex interactions between limiting nutrients and this topic has to be considered in experimental and theoretical studies investigating nutrient‐limited growth responses of animals to accurately assess consequences for population dynamics.